Current evidence on improving influenza vaccine uptake in low- and middle-income countries: A scoping review of determinants and interventions - Prima Alam; Lerato Tsotetsi; Tshepiso Msibi; Mulalo Mashamba; Janan Dietrich (Vaccine: X)
Influenza is a vaccine-preventable disease affecting three to five million individuals across the globe annually. Low- and middle-income countries (LMICs) bear substantial health and economic consequences of influenza-related mortality. Despite this disproportionate burden, influenza vaccinations are seldom used across LMICs. In this article, we reviewed current evidence on improving influenza vaccine uptake within LMICs by examining key determinants and interventions. We conducted a scoping review of peer-reviewed studies pertaining to influenza vaccine uptake in LMICs. We searched five electronic databases for articles published 2014–2024, using terms relating to influenza vaccines, interventions, and context. Twenty-four articles met the inclusion criteria with sample sizes ranging from 38 to 9420. The authors followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines and synthesized the included articles using thematic analysis.All studies included in this review were cross-sectional and primarily used quantitative surveys. Most of the included studies were conducted in Sub-Saharan Africa (South Africa, Kenya, Malawi, and Sierra Leone) and the Middle East and North Africa (Tunisia, Jordan, Lebanon, and Egypt). Articles predominantly targeted vulnerable populations including elderly, pregnant women, and young children as well as healthcare workers. Participants across the included studies reported high levels of willingness to receive the influenza vaccination but lower levels of uptake. Having positive perceptions and attitudes towards the efficacy and safety of the vaccine, greater belief in disease susceptibility, physician recommendations, and a history of being vaccinated were associated with greater willingness to receive the influenza vaccine. Six articles explored national campaigns or researcher-led interventions to improve influenza vaccine uptake with educational campaigns positively changing attitudes towards influenza vaccination and integration of year-round vaccination campaigns with routine services as an effective vaccine delivery method.